ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PADA MATERI OPERASI BILANGAN BULAT DI KELAS VII SMP NEGERI 1 SUWAWA - Elan Husaini; Majid Majid; Dewi Rahmawaty Isa (MES: Journal of Mathematics Education and Science, 2026)
Mathematics is a fundamental science that plays an important role in developing students' logical, critical, and analytical thinking skills. One of the main competencies in mathematics learning is conceptual understanding, but international evaluation results and field findings show that this ability is still relatively low, especially in the subject of integer operations. This study aims to analyse students' mathematical concept comprehension skills in integer operations in Grade VII at SMP Negeri 1 Suwawa. The study used a quantitative descriptive method conducted at SMP Negeri 1 Suwawa, Bone Bolango Regency, Gorontalo, with 21 students selected through purposive sampling. The research instruments consisted of an eight-question essay test that had been validated and reliability checked, as well as semi-structured interviews. The data were analysed using descriptive analysis techniques through the calculation of mean scores, standard deviations, and percentages, then grouped into high, medium, and low categories based on four concept understanding indicators. The results showed that 67% of students were in the medium category, 19% in the high category, and 14% in the low category. The indicator of recalling concepts was the most mastered by students, while the indicators of selecting procedures and applying concepts in problem solving were the most challenging. These findings indicate that most new students have mastered procedural understanding but have not yet achieved deep conceptual understanding. Therefore, learning strategies that emphasise meaningful activities and the use of various representations are needed to improve students' understanding of mathematical concepts.